Handbook of organizational learning and knowledge management - Easterby-Smith, Mark; Lyles, Marjorie A. (Wiley, 2011)
"The fully revised and updated version of this successful Handbook is welcomed by management scholars world-wide. By bringing together the latest approaches from the leading experts in organizational learning & knowledge management the volume provides a unique and valuable overview of current thinking about how organizations accumulate 'knowledge' and learn from experience. Key areas of update in the new edition are:[bullet] Resource based view of the firm[bullet] Capability management[bullet] Global management[bullet] Organizational culture[bullet] Mergers & acquisitions[bullet] Strategic management[bullet] Leadership"--